"At My Age … ": Defining Sexual Wellness in Mid- and Later Life. Issue 7 (2nd September 2019) - Syme, Maggie L.; Cohn, Tracy J.; Stoffregen, Sydney; Kaempfe, Hanna; Schippers, Desiree
Abstract : Sexual wellness is integral to quality of life across the life span, despite ageist stereotypes suggesting sexual expression ends at midlife. However, conceptualizing sexual wellness in mid- and later life is complicated by a dysfunction-based narrative, lack of a sex-positive aging framework, and existing measures that are age irrelevant and limited in scope. This study aimed to address these limitations by providing a conceptualization of sexual wellness grounded in definitions from midlife and older adults. A sample of 373 midlife and older adults ( M = 60, SD = 5.84) in the United States provided a definition of sexual wellness. Using thematic analysis, multiple researchers coded qualitative responses, and results suggested a biopsychosocial-cultural framework. Findings reflect that midlife and older adults provide multifaceted definitions inclusive of various behavioral experiences, including disengaging from sex. They are also keenly aware of physical and psychological limitations and strengths, and emphasize mutual experiences and synchronicity. Midlife and older adults also reflect on age, drawing comparisons to different phases of life and often displaying adaptability in adjusting expectations. When conceptualizing sexual wellness in this population it is imperative to capture this multidimensionality, include those who are not actively engaging in sex, and be aware of the influence of ageist and dys/function narratives.